Resiliensi Psikologis Guru dalam Menghadapi Burnout pada Transformasi Pendidikan - Ayu Andini (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Classroom management skills are essential competencies that teachers must possess in creating effective and conducive learning processes. In Arabic language learning at the Madrasah Ibtidaiyah level, classroom management is not only related to pedagogical competence but also to the implementation of teachers’ professional ethics in interacting with students. Problems identified in this study indicate challenges in creating an active, orderly, and enjoyable classroom atmosphere, particularly in Arabic language learning for grade 3 students at MI Assholach. This study aims to analyze classroom management skills from the perspective of the professional ethics of Arabic language teachers in grade 3 at MI Assholach. The study employed a descriptive qualitative approach with a case study design. The research subjects consisted of Arabic language teachers, third-grade students, and the headmaster. Data collection techniques included observation, interviews, and documentation, while data analysis involved data reduction, data presentation, and conclusion drawing. The findings reveal that teachers have implemented various classroom management strategies, such as seating arrangements, learning motivation, interactive methods, and persuasive approaches toward students. The implementation of professional ethics is reflected in discipline, responsibility, patience, and effective communication between teachers and students. This study concludes that classroom management skills supported by professional ethics are able to create effective and conducive Arabic language learning. Therefore, continuous improvement of teachers’ pedagogical competence and professionalism is necessary